The iron fist in the velvet glove? Testing the militarization/community policing paradox - Koslicki, Wendy M. (International journal of police science & management, 2018)
A number of police militarization scholars have explored the paradox of the simultaneous emergence of community policing and militarism in the United States. Several researchers have suggested that police militarization and community policing may be cohesive strategies of state control, with community policing being the “velvet glove” that wraps the “iron fist” of militarization in palatable rhetoric. Alternatively, it has been suggested that these two policing strategies are incoherent, having emerged as a result of the state’s disorganized attempts to maintain control in the face of significant societal changes. To date, little research has examined the link between community policing and police militarization specifically. This study uses community policing data from the 2013 LEMAS survey to examine variation in military equipment acquisition data from the Department of Defense’s 1033 Program between the years 2012 and 2014. Results show that departments engaging in certain community policing activities are significantly less likely to acquire general military equipment, firearms, and military vehicles. These findings suggest that these policing strategies are not necessarily coherent and potentially support the argument that community policing efforts can buffer militarization. However, these results also highlight the need for more empirical research on existing theories of militarization, as well as the causes and effects of police militarism and community policing activities.